Development of Composite Adsorbent Coating Based Acrylic Polymer/Bentonite for Methylene Blue Removal - Azha, Syahida Farhan; Abd Hamid, Shazlina; Ismail, Suzylawati (Journal of Engineering and Technological Sciences, 2017)
The development of composite adsorbent coating based acrylic polymer solution (APS) mixed with bentonite (ben) was investigated. The composite adsorbent coating was prepared and coated to a high surface area substrate, cotton cellulosic fiber (CCF). The APS/ben-CCF was used for a single cationic methylene blue (MB) dye adsorption system. Characterization of composition and structure of materials and coating was carried out by X-ray fluorescence (XRF), scanning electron microscopy (SEM), and UV-spectroscopy (UV-VIS). The adsorption properties of the APS/ben-CCF were investigated as a function of solution pH, initial dye concentration and contact time as well as solution temperature of MB dye. The result revealed that the APS/ben-CCF functioned well in solutions of various pH (acidic to alkaline), achieving 100% removal of MB within 2 hours of adsorption for 50 ppm. Kinetic studies showed that APS/ben-CCF is endothermic in nature since the adsorption capacity increased with increasing solution temperature. These results demonstrate that APS/ben-CCF composite adsorbent coating is an advanced adsorbent with advantages such as easy phase separation and capability to remove cationic dyes in a short time period.